2021
DOI: 10.5114/biolsport.2021.101604
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of dynamic versus foam rolling warm-up strategies on physical performance in elite tennis players

Abstract: To date, there is a lack of information about the optimal conditions of the warm-up to lead to a better performance in elite tennis players. The aim of this study was to compare the effects of two different warm-up protocols (dynamic vs. self-myofascial release with foam rolling) on neuromuscular variables associated with physical determinants of tennis performance. Using a crossover randomised experimental design, eleven professional men tennis players (20.6 ± 3.5 years) performed either a dynamic warm-up (DW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 37 publications
(50 reference statements)
1
49
0
Order By: Relevance
“…Thus, further studies are warranted. Based on the current literature, athletes should focus on specific preparation before participating in their desired discipline [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further studies are warranted. Based on the current literature, athletes should focus on specific preparation before participating in their desired discipline [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous investigations on the effects of MFR on jumping performance provide disagreeing evidence, highlighting that MFR can either enhance it or be similar to dynamic warm ups, but could also result in a performance reduction if applied for more than 1 min [ 70 72 ]. In addition, as described in the previous paragraph, also in MFR studies vertical jumps are more frequently employed to assess lower limb performance.…”
Section: Discussionmentioning
confidence: 99%
“…There was only a 1.79% difference between subelite and novice athlete times. Interestingly, only one group of researchers used elite males as their participants (34). The elite group was made up of 11 subjects with an average performance of 2.75 seconds, which was the same for subelite athletes and only 1.79% faster compared to novice athletes.…”
Section: Methodsmentioning
confidence: 99%
“…Like the traditional 5-0-5 COD test, we cannot comment on the interaction between sex and sport as no research groups have reported male and female COD times in the same sport for the modified 5-0-5 COD test. Nevertheless, 6 out of the 9 studies that reported performance data have involved tennis athletes (16,17,21,34,41,43). This makes sense as the movement patterns of the modified 5-0-5 COD test are very similar to movements performed during a tennis match.…”
Section: Sportmentioning
confidence: 99%